Proceedings of the 2020 CHI Conference on Human Factors in Computing Systems 2020
DOI: 10.1145/3313831.3376866
|View full text |Cite
|
Sign up to set email alerts
|

DFSeer: A Visual Analytics Approach to Facilitate Model Selection for Demand Forecasting

Abstract: Selecting an appropriate model to forecast product demand is critical to the manufacturing industry. However, due to the data complexity, market uncertainty and users' demanding requirements for the model, it is challenging for demand analysts to select a proper model. Although existing model selection methods can reduce the manual burden to some extent, they often fail to present model performance details on individual products and reveal the potential risk of the selected model. This paper presents DFSeer, a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 59 publications
0
19
0
Order By: Relevance
“…Dove et al [209] surveyed to understand how design innovation is practiced in the ML domain in terms of user experience. [63], [70], [165], [174], [211] [124], [125], [128], [175], [217] [69], [112], [113], [118], [130], [131], [133], [135], [137], [140], [144], [152], [153], [155] [49], [57], [67], [98], [110], [114], [180], [192], [193], [203], [214], [215] [48], [59], [62], [75], [79], [111], [120], [156], [159], [185], [195], [197], [207], [218] [65], [83],…”
Section: Survey Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Dove et al [209] surveyed to understand how design innovation is practiced in the ML domain in terms of user experience. [63], [70], [165], [174], [211] [124], [125], [128], [175], [217] [69], [112], [113], [118], [130], [131], [133], [135], [137], [140], [144], [152], [153], [155] [49], [57], [67], [98], [110], [114], [180], [192], [193], [203], [214], [215] [48], [59], [62], [75], [79], [111], [120], [156], [159], [185], [195], [197], [207], [218] [65], [83],…”
Section: Survey Resultsmentioning
confidence: 99%
“…Iconate [ 119 ] is a tool created to generate complex icons based on text queries. Sun et al [ 120 ] present a system to aid model selection for demand forecasting. Im et al [ 121 ] attempted to create an application to derive social signals for online social platforms computationally.…”
Section: Classifying Hcml Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…However, demand forecasting models are facing the challenge of market uncertainty and data complexity. In this regard, the study presented in [47] focused on developing a VA system to demonstrate the performance of various models in order to support decision makers in selecting the best performing model for their demand forecasting activities. Both manufacturers and retailers can benefit from such models towards facilitating their model selection tasks.…”
Section: ) Plan Processesmentioning
confidence: 99%
“…Most AutoML systems use performance metrics as basis for model evaluation and ranking. However, research on model analytics and comparison of manually-built models has shown that none of the stakeholders are satisfied to only see performance metrics [21,23,28,29,35]. They are interested in details such as types of errors, how models perform on specific instances, and a detailed reasoning by which models make predictions.…”
Section: Introductionmentioning
confidence: 99%